Impact of the Expansion of Private Brands on Korean Retail and Manufacturing - Jin Kook Lee (KDI Journal of Economic Policy, 2018)
The private brands (PB) of corporate retailers are booming in Korea. This paper examines the effect of the rise of PB on Korean retail and manufacturing. By utilizing both store-level data and firm-level data, I find that the expansion of PB elevates the profits of corporate retailers but does not significantly affect, and in some cases even reduces, those of subcontracting manufacturers. This occurs not only because sales of national brands (NB) decline due to the launch of similar PBs but also because the imbalance in the bargaining positions of the two parties has caused retail margins to be set high while manufacturers' operating profits are set low. The paper provides policy recommendations for fair contracts and cooperative development between retail and manufacturing companies.
Keywords: L11; L13; L16; L22; L81; 330; Private brands; Store brands; Retailers; Buyer power